DIAGNOSTIC AND TREATMENT APPROACHES TO ACUTE PANCREATITIS IN PREGNANT WOMEN - Mishchenko, V.V.; Mishchenko, V.P.; Rudenko, I.V.; Pustovoit, P.I.; Likhachov, V.K.; Dobrovolska, L.M.; Makarov, O.G. (World of Medicine and Biology, 2022)
The frequency of acute pancreatitis is from 1:1500 to 1:10000 pregnancies. The purpose of the study was to improve diagnostic and treatment approaches for acute pancreatitis in pregnant women. 21 pregnant women who were diagnosed with acute pancreatitis were under supervision. The diagnosis of acute pancreatitis in pregnant women was based on the Atlanta classification criteria (2013). Complex conservative treatment of acute pancreatitis in pregnant women consisted of prescribed octreotide, proton pump inhibitors, in the II trimester ‒ protease inhibitorssemi-syntheticic penicillins, cephalosporins of the III-IV generations. It is necessary to correct the water-electrolyte balance, compensate for plasma loss, microcirculation disorders, fight against edema of the pancreas and parapancreatic tissue. The course of acute pancreatitis in pregnant women in 52.4 % of cases was characterized by an average and severe degree of severity, which was accompanied by distress and the threat of fetal death. There were no fatalities. The implementation of the diagnostic and treatment approaches used by us in acute pancreatitis in pregnant women made it possible to avoid mortality, surgical and obstetric‒perinatal complications. Management of pregnant women with acute pancreatitis is an extremely difficult task and primarily depends on the severity of acute pancreatitis in pregnant women. The management of pregnant women suffering from acute pancreatitis requires a multidisciplinary approach to predict the course of pancreatitis, determine the tactics of managing pregnancy and acute pancreatitis in pregnant women, the method and timing of delivery.
Keywords: management of pregnant women; acute pancreatitis; multidisciplinary approach